Interferensi dalam Dialog Film Rudy Habibie Sutradara Hanung Bramantyo - Apriliani, Dewi; Herwandi, Herwandi (UIR Press, 2023)
This research aims to describe and analyze interference at the phonological and morphological levels in the dialogues of the movie